Characterization and in vitro expression studies of a potential xenogeneic DNA vaccine against canine mammary tumours - YADAV, PAVAN KUMAR; GUPTA, SHISHIR KUMAR; KUMAR, SAROJ; SAINI, MOHINI; MISHRA, SUMIT RANJAN; NANDAKUMAR, P; KATARIA, MEENA (The Indian Journal of Animal Sciences, 2018)
Matrix metalloproteinases-7 (MMP-7) which is expressed in a wide variety of malignant cells has been seen tobe extensively up-regulated in mammary carcinomas. MMP-7 can promote cancer invasion and angiogenesis through proteolytic cleavage of extracellular matrix and basement membrane proteins. This property of MMP-7 makes it a promising target in the context of immunotherapy. Further, to enhance DNA-based immunization, a cytokine gene can be employed as an adjuvant. Interleukin-18 (IL-18) is a Th1-type cytokine that has been demonstrated as a potential biological adjuvant in murine tumour models. The present study was undertaken to clone murine MMP-7 (mMMP-7) and IL-18 genes in pVIVO2.mcs eukaryotic expression vector and to characterize their expression by immunofluorescence and Western blotting. This double gene construct now may be used as a potential xenogeneic DNA vaccine against canine tumour model.